Sami identity in the face of climate change - Kaczmarek, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Global warming is accelerating, thus irreversibly changing the human environment, and most of the measures taken to halt this phenomenon seem to be the result of wishful thinking. Policies meant to combat climate change fail to bring about the desired effect. Arctic indigenous peoples are particularly vulnerable to climate change, and their cultural identity is under threat. However, owing to the actions taken by state authorities and European Union institutions, there is a chance that the Sami languages will be preserved.
Keywords: global warming; Finland; Lapland; Sami people; European Union; indigenous peoples